Peranan Aset Komunitas dalam Pemberdayaan Perempuan Nelayan Puspita Bahari Morodemak Jawa Tengah - Wina Rosalina; Suciati Suciati (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This paper will review the development of an Islamic community initiated by the Puspita Bahari organization to Muslim fisherwomen in the village of Morodemak. The background of this empowerment is due to the problem of fisherwomen who work hard to find debt to meet family needs due to the uncertainty of their husband's income. This woman also experienced violence from her husband. The Puspita Bahari organization is here to invite women to be independent, to increase family finances, and to get out of poverty. This empowerment takes the form of first helping to provide welfare guarantees for fisherwomen who go to sea with recognition of status on the KTP from housewives to become fishermen. The second empowerment is to invite fisherwomen to work by making processed fish products in the form of crackers, chips, shredded so they can sell fish at a higher price. Puspita Bahari's empowerment is the empowerment of Islamic community development based on the development of community assets. The method used is library research based on websites, journals, and articles available on the internet. The findings found that there are 6 assets that are used in empowerment, for example the role of environmental assets in the form of the sea and the wealth of fish to become raw materials for processed products. The theory that will be used is the role of community assets in the development of Islamic society.